The validity of resting energy expenditure predictive equations in adults with central obesity: A sub-sample of the RaNCD cohort study. Issue 3 (September 2019) - Pasdar, Yahya; Moradi, Shima; Hamzeh, Behrooz; Najafi, Farid; Nachvak, Seyed Mostafa; Mostafai, Roghayeh; Abdollahzad, Hadi; Nelson, Michael
Background: There are different equations for estimating Resting Energy Expenditure (REE). However, these equations were mainly developed based on populations of western countries. Aim: The present study was conducted to determine the validity of REE predictive equations in adults with central obesity. Methods: This study was conducted with 129 adults with central obesity aged 35–65 years, a sub-sample from a large cohort study (Western Iran), Kurdish population. REE was measured by indirect calorimetry (IC) and REE predictive equations. Data were analysed using Pearson correlation, paired t-test, concordance correlation coefficient (CCC), mean squared deviation (MSD), level of agreement (LOA) and Bland-Altman plot. Results: All REE predictive equations had low CCC and high LOA. Although there was no statistically significant difference in the REE measured with IC and the REE predicted with the Food and Agriculture Organization/World Health Organization/United Nations University (FAO/WHO/UNU), FAO/WHO/UNU (Height), Muller and revised Harris-Benedict equations ( P = 0.874, 0.113, 0.619, 0.143 and P = 0.121), other equations had statistically significant differences with IC ( P <0.001). In addition, the highest correlation was found between the IC (r = 0.682). The least difference was related to the FAO/WHO/UNU equation, with an agreement limit of -507.96 to 500.79 Kcal/day, with a 95% confidence interval. Conclusions: The results of this study showed that the FAO/WHO/UNU, Muller, revised Harris-Benedict equations and Mifflin St Jeor equations are relatively acceptable for estimating REE. However, these prediction equations are not good at predicting REE; more precise equations are needed to apply for different ethnic groups.